Comparative analysis of alectinib and brigatinib in real-world treatment of advanced NSCLC with ALK rearrangements - Kyuhwan Kim; Kyu Yean Kim; Hye Seon Kang; Ah Young Shin; Sung Kyoung Kim; Chan Kwon Park; Sang Haak Lee; Seung Joon Kim; Jeong Uk Lim; Chang Dong Yeo (Therapeutic Advances in Medical Oncology)
Background and objectives: This study aimed to compare the efficacy of the second-generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs) alectinib and brigatinib in the treatment of advanced non-small-cell lung cancer (NSCLC) with ALK rearrangements based on real-world data. Design and methods: We conducted a multicenter retrospective study using the Clinical Data Warehouse from seven university hospitals affiliated with the Catholic Medical Center. Patients diagnosed with ALK-positive advanced NSCLC and treated with alectinib or brigatinib were included. Key outcomes such as time to discontinuation (TTD), duration of response (DOR), overall survival (OS), and objective response rate (ORR) were analyzed. Results: A total of 143 patients were included (107 treated with alectinib, 36 with brigatinib). Alectinib was more frequently used as a first-line treatment (71% vs 44.4% for brigatinib, p  = 0.008). Prior crizotinib treatment was more frequent in the brigatinib group (52.8% vs 22.4% for alectinib, p  < 0.001). The best ORR was similar between the groups (84.1% for alectinib vs 83.3% for brigatinib, p  = 0.518). The median TTD was 57.8 months (95% confidence interval (CI): 29.0–86.7) for alectinib and 39.6 months (95% CI: 21.7–57.4) for brigatinib ( p  = 0.462). No significant differences were observed in intracranial TTD, intracranial DOR, or OS between the groups. Prior crizotinib treatment significantly shortened TTD for second-generation TKIs ( p  = 0.025), but the overall TKI treatment duration did not show a significant difference between patients who received frontline second-generation ALK TKIs and those who received second-generation ALK TKIs sequentially after crizotinib. Conclusion: Alectinib and brigatinib demonstrated comparable efficacy in ALK-positive advanced NSCLC. Undergoing crizotinib followed by a second-generation TKI was not significantly different from initiating a second-generation TKI without prior crizotinib in terms of outcomes.